The Concept “Student Experience” from the Point of View of Philosophical Anthropology and Developmental Psychology - V. S. Efimov; A. V. Laptevа (Высшее образование в России)
An actual topic in higher education research today is the study of student experiences. It is believed that knowledge of educational settings, the degree of student involvement in educational and extracurricular activities, satisfaction with the quality of courses or practices offered, etc. helps to retain the student population, modernize educational programs, university campus services, etc. The study presents a new concept of student experience, corresponding to the key position of the university as an institution for the development of human and society. Research methods are conceptual analysis and conceptual design.Ideas about the “student experience” and the need to study its components are determined by the models of relations between the university and students. Currently, universities widely use the “instruction-based” and “consumer” models, and new models such as the “co-production” or “transformative learning” model are also being tested.The article examines the “anthropic” model of relations between the university and students, which 1) reflects the civilizational mission of the university; 2) is based on philosophical and anthropological ideas about the formation of an individual person as a “path” on which he/she discovers new realities (“horizons”) of personal and professional existence; 3) sets a new direction for research on student experience.A new concept of student experience is proposed, correlated with the “anthropic” model of relations between the university and students. Significant components of such experience are: “discovering others” who are carriers of a new (for the student) self-determination, thinking, worldview, and way of action; “shift of the horizon” – the discovery of new meanings, objects, transformation of consciousness (changing its schematisms and categories); mastering a new life world; overcoming the existing ways and patterns of thinking and action, personal limitations and building a new self; reflection of one’s path and “assembling oneself” through personal history.This concept of student experience will allow us to build educational practices that are adequate to the needs of active students focused on complex educational experiences – the path of discovery and transformation of consciousness and thinking